From water to edible fish. Transfer of metals and metalloids in the San Roque Reservoir (Córdoba, Argentina). Implications associated with fish consumption. (April 2016) - Monferrán, Magdalena V.; Garnero, Paola; de los Angeles Bistoni, María; Anbar, Ariel A.; Gordon, Gwyneth W.; Wunderlin, Daniel A.
Highlights: Hg showed consistent biomagnification throughout different components of the food web. Most elements were bioaccumulated from water to plankton with further biodilution to higher trophic levels. Differential accumulation of studied elements among diverse fish tissues was observed. Hg, As and Cr were bioaccumulated in fish from food. Toxic elements freely put into the environment can be biomagnified and reach human food. Abstract: The concentration of Mn, Fe, Zn, Cu, Cd, Cr, Ni, Ag, Mo, Nd, Al, Ce, As, Sr, Pb, Pt and Hg was analysed in water, sediments, and aquatic organisms from the San Roque Reservoir (Córdoba-Argentina), sampled during the wet and dry season, to evaluate their transfer through the food web. Stable nitrogen (δ 15 N) isotopes were used to investigate trophic interactions. According to this, samples were divided into three trophic groups: plankton, shrimp ( Palaemonetes argentinus ) and fish (Silverside, Odontesthes bonariensis) . Liver and gills are the main heavy metal storage tissues in fish. Hg and As concentrations in the muscle of O. bonariensis exceed the Oral Reference doses for metals established byUSEPA (2009) . Trophic magnification factors (TMFs) for each element were determined from the slope of the regression between trace element concentrations and δ 15 N. Calculated TMFs showed fundamental differences in the trophodynamics of the studied elements during the wet and dry season in the San Roque Reservoir. Concentrations of Ni, Cd, Cr, Al, Mn, Fe, Mo, Ce, Nd, Pt and Pb during both seasons, and Sr during the dry season, showed statistically significant decreases (TMF < 1) with increasing trophic levels. Thus these elements were trophically diluted in the San Roque food chain. Conversely, Cu, Ag and As (dry season) showed no significant relationships with trophic levels. Among the elements studied, Hg in the wet season, and Zn in the dry season were the only ones showing a statistically significant increase (TMF > 1) in concentration with trophic level. Current results trigger the need for further studies to establish differential behaviour with different species within the aquatic web, particularly when evaluating the transfer of toxic elements to edible organisms, which could pose health risks to humans.